Characteristics of auditors' non-audit services and accruals quality in Malaysia. Issue 2 (27th January 2020) - Effiezal Aswadi Abdul, Wahab; Nik Abdul Majid, Wan Zurina; Harymawan, Iman; Agustia, Dian
Abstract : Purpose: The purchase of non-audit services from incumbent auditors has generated considerable attention. This study aims to examine the relationship between characteristics of non-audit services, namely, the recurrence and types of services, and accruals quality in Malaysia. Design/methodology/approach: This study analyzed hand-collected audit and non-audit fees of 1, 117 observations from Malaysian firms from 2009 to 2011. This study used descriptive analysis, univariate tests and multivariate regression to investigate the potential effect of non-audit services on accruals quality. Findings: Non-audit services are associated with lower accruals quality. Recurring and non-recurring non-audit service fees are detrimental to the quality of accruals, as are all types of recurring non-audit services. Only non-recurring audit-related services decrease accruals quality. The results demonstrate that provisions of non-audit services create economic bonding, and thus a threat to auditor independence. Results remain robust with the inclusion of corporate governance and institutional variables. Research limitations/implications: The sample period might represent a limitation as it only covers three years of data. This limitation is mainly because of the nature of data collection of the non-audit services fees. Practical implications: The findings could suggest a refinement on the Malaysian Institute of Accountants (MIA) by-laws focusing on auditor independence, and it could assist other regulative bodies such as the Securities Commission, the stock exchange (Bursa Malaysia) in ensuring better governance on the provision of non-audit services. Originality/value: This study is the first that provides evidence on the relationship between non-audit services, types, and recurring and non-recurring non-audit services and accruals quality in Malaysia.